The Effect of Problem Posing Model on University Students’ Creativity and Problem-Solving Skills - Fatimah Djafar (AL-ISHLAH: Jurnal Pendidikan, 2022)
One of the goals of education is to prepare graduates to compete in a world of work that has undergone massive social and technological changes. For this reason, an ideal education should develop several skills that must be mastered in the 21st century, including problem-solving skills and creativity. This study aims to determine the impact of the problem-posing learning model on problem-solving creativity skills in learning statistics. A quasi-experimental research design is used in this study involving 29 students. Data were collected using two questionnaires, namely problem-solving skills creativity skills questionnaires. The data that has been collected is then analyzed quantitatively using SPSS 20.00 by running a t-test. The results showed that the problem-posing learning model was proven to have a significant positive impact on problem-solving and creative thinking skills compared to classes using conventional learning models.